The Impact of External Locus of Control, Professional Commitment, and Acceptance of Client Explanations on Premature Audit Sign-Off Among Public Auditors: The Moderating Role of Time Budget Pressure - Sugiyarto, Sugiyarto; Hastuti, Theresia Dwi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Auditors hold a critical role in providing objective assessments of financial statement accuracy and fairness. However, audit integrity faces challenges, notably premature sign-off, which risks compromising audit validity and potentially leading to inaccurate financial statements that affect stakeholders. This study examines factors influencing premature sign-off, specifically external locus of control, professional commitment, and a tendency to readily accept client explanations, with time budget pressure as a moderating variable. Using survey data from 72 auditors in Semarang public accounting firms, hypotheses were tested through multiple regression and moderation analysis. Findings reveal that external locus of control and readily accepting client explanations positively influence premature sign-off, while professional commitment has a significant negative effect. Time budget pressure significantly moderates the relationships between external locus of control and professional commitment with premature sign-off, though it does not significantly affect the relationship with readily accepting client explanations. These insights enhance understanding of auditor behavior and audit quality.